The Role of Public Administration in Strengthening Sustainable Rural Food Systems in Manurung Village, Bola District, Wajo Regency - Asrijal Asrijal; Besse Herlina; Andi Bagas Sulungkau; Darmawan Sanusi; Ambo Upe (Educational Dynamics: International Journal of Education and Social Sciences, 2026)
This study aims to identify the supporting and inhibiting factors affecting the role of public administration in strengthening rural food systems and to formulate strategies for optimizing public administration to achieve sustainable rural food systems. The study was motivated by the strategic role of public administration in planning, organizing, coordinating, implementing policies, and monitoring food development programs. A mixed-methods approach combining qualitative and quantitative techniques was employed. Informants included village officials, farmer groups, community leaders, and community members selected through purposive sampling. Data were collected through focus group discussions (FGDs), in-depth interviews, observations, and documentation, and analyzed using the Pearce and Robinson (2009) model. The findings indicate that Manurung Village possesses several supporting factors, including extensive agricultural land, available local labor, supportive village regulations, active farmer groups, and village funds allocated to the food sector. External opportunities include government food security programs, access to digital markets, agricultural empowerment initiatives, private-sector partnerships, and increasing local food consumption. Major constraints consist of limited administrative capacity, suboptimal program management, inadequate irrigation infrastructure, dependence on middlemen, limited agricultural innovation, climate change, commodity price fluctuations, land conversion, external competition, and dependence on subsidized fertilizers. IFAS analysis produced a strength score of 2.28 and a weakness score of 0.72, indicating that existing strengths can overcome internal weaknesses. The recommended strategy is the SO (Strength–Opportunity) strategy, which emphasizes maximizing internal strengths while utilizing external opportunities to support a sustainable rural food system.